Hamilton & Hardy's industrial toxicology - Harbison, Raymond D.; Bourgeois, Marie M.; Johnson, Giffe T. (Hoboken, New Jersey : Wiley, 2015)
"This book provides comprehensive coverage of all aspects of industrial toxicology, employing a succinct chapter format that has become the hallmark for the previous editions of Hamilton & Hardy's Industrial Toxicology"--Provided by publisher.
Mode of ActionOccupational Exposure; Risk Assessment; References; Chapter 11: Boron; Background and Uses; Physical and Chemical Properties; Environmental Fate and Bioaccumulation; Ecotoxicology; Mammalian Toxicology; Sources of Exposure; Industrial Hygiene; References; Chapter 12: Cadmium; Background and Uses; Physical and Chemical Properties; Environmental Fate and Bioaccumulation; Ecotoxicology; Mammalian Toxicology; Sources of Exposure; Industrial Hygiene; Risk Assessments; References; Chapter 13: Chromium; Background and Uses; Physical and Chemical Properties
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on July 17, 2015).
Keywords: Industrial toxicology; Hazardous Substances -- toxicity; Occupational Exposure; Occupational Health; Risk Assessment; MEDICAL -- Toxicology; Industrial toxicology; Electronic books